CLASS MANAGEMENT IN IMPROVING THE QUALITY OF ISLAMIC BOARDING SCHOOL EDUCATION - Lisah, Nora; Sholihah, Imroatus; Abdullah, Abdullah; khoir, Muhammad ilzamul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research focuses on the decline in student learning motivation in the digital era and how educational management can overcome this challenge. The aim of this research is to determine the factors that influence students' learning motivation, including teachers' digital skills, changes in students' thinking patterns, mental health impacts and psychological burden. This research uses a qualitative approach with in-depth interview techniques to collect data from students and teachers at Banyuwangi High School. Data analysis was carried out thematically to identify relationships between these variables. The research results show that adequate teacher digital skills, environmental support in changing mindsets, and effective stress management can significantly increase student learning motivation. The implications of this research emphasize the importance of developing teachers' digital skills, adaptive learning strategies, and attention to students' mental health in order to achieve quality education in the digital era.